JOB SATISFACTION EFFECT ON ORGANIZATIONAL COMMITMENT THROUGH TRUST AS A MEDIATING VARIABLE FOR PRIVATE VOCATIONAL SCHOOL (SMK) TEACHERS IN CENTRAL JAKARTA - Masayu Rifdah Fakhirah Novianawati; Widya Parimita; Susan Febriantina (Econosains Jurnal Online Ekonomi dan Pendidikan, 2021)
This study aims to determine the effect of job satisfaction on organizational commitment through trust as a mediating variable in private vocational school teachers in Central Jakarta. This study uses a survey method with a descriptive approach. The population in this study amounted to 200 respondents with a sample of 133 respondents. The model used in this study is a relationship or influence model, or called path analysis. To test the hypothesis proposed in this study, the model fit analysis technique used is Structural Equation Modeling (SEM) which is operated using the SmartPLS 3.0 program. The results showed that job satisfaction had an effect on organizational commitment through trust as a mediating variable. Original Sample value of the influence of the three variables is 0.449 and T-Statistic > 1.96 which is 3.889. Furthermore, based on P-Value 0.000 <0.05, the variable job satisfaction has an indirect effect on organizational commitment through trust as a mediating variable.